2010
DOI: 10.1002/bdm.649
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating advisors: A policy‐capturing study under conditions of complete and missing information

Abstract: Decision-makers' relative preferences for various advisor characteristics were investigated in two multilevel policy-capturing studies. The characteristics under consideration were: advisor expertise, advisor confidence, advisor intentions, and whether that advisor was the sole available source of advice. In Study 1, decision-makers had access to all relevant information about the advisors. In contrast, some relevant information about the advisors was systematically made unavailable in Study 2, which allowed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 68 publications
2
44
0
Order By: Relevance
“…Furthermore, in accordance with previous findings (e.g. Bonaccio & Dalal, ), we find increased receptiveness to advice from an expert. Importantly, we show that this effect works through the proposed mechanism of perceived justifiability and anticipated regret.…”
Section: General Discussion and Conclusionsupporting
confidence: 93%
“…Furthermore, in accordance with previous findings (e.g. Bonaccio & Dalal, ), we find increased receptiveness to advice from an expert. Importantly, we show that this effect works through the proposed mechanism of perceived justifiability and anticipated regret.…”
Section: General Discussion and Conclusionsupporting
confidence: 93%
“…Instead, an other‐focused emotion that is positive (such as gratitude, love, or desire) conveys that another person's abilities, motivations, or needs are in line with or even exceed one's own wishes or demands (Haidt, ; McCullough et al, ). Following Bonaccio and Dalal (), who showed that evaluations of advisors are primarily determined by inferences about the advisors' abilities and motivations, we predict that others will be perceived as being more able to provide good advice. Consequently, their advice will have more influence on one's decisions when the decision maker experiences an other‐focused emotion, which is positive rather than negative.…”
Section: A Parsimonious Explanation Of Emotions In Advice Takingmentioning
confidence: 91%
“…Prior research suggests that advisors' expertise and confidence are among the most influential advisor characteristics shaping advice taking (Bonaccio & Dalal, 2010). Moreover, people appear to attend to relatively subtle cues and signals to create judgments of advisors; for example, advisors' confidence seems to serve as a heuristic influencing whether they are perceived to have expertise, taskrelated knowledge, or accurate advice (Sniezek & Van Swol, 2001).…”
Section: Advice Takingmentioning
confidence: 96%